Characterization of asiaticoside concentration, total phenolic compounds, and antioxidant activity of different varieties of Centella asiatica (L.) and essential oil extraction using hydro-distillation with enzyme assisted - Abu Bakar, Izza Nadira; Ibrahim, Mohamad Faizal; Hakiman, Mansor; Abd-Aziz, Suraini; Prasongsuk, Sehanat; Cheong, Lily Yen Tin; Jenol, Mohd Azwan (Elsevier, 2022)
Centella asiatica (L.) or known locally as Pegaga has been recognized by Ministry of Agriculture (MoA) Malaysia as one of the top 10 the best herbs in Malaysia. Considering its beneficial advantages, the varieties of C. asiatica in Malaysia have been compared and further investigated for its potential to produce essential oil. In this study, the bioactive compounds, total phenolic content (TPC) and antioxidants activity from different varieties of Centella asiatica (L.) known as Pegaga Kampung, Pegaga Nyonya and Pegaga Salad from Malaysia and Pegaga Thailand have been determined followed by the extraction of essential oil using hydro-distillation (HD) and hydro-distillation with enzyme assisted (HDEA). Findings showed that Pegaga Kampung had the highest asiaticoside content of 0.259 mg/g, TPC of 9.22 mg GAE/g and DPPH radical scavenging activity (DPPH*) of 76.88% in leaf, 67.77% in petiole, and 60.37% in root as compared to other varieties of C. asiatica. Extraction of essential oils from Pegaga Kampung using HDEA with 40 FPU/gsubstrate of cellulase produced the highest yield of 1.01%. A higher TPC of 107.05 mg GAE/100 g was detected in essential oils extracted using HDEA with 10 FPU/gsubstrate of cellulase, whereas the highest DPPH* of 19.02% was found in essential oil using HD.